Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1128/mcb.19.11.7549
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization between Members of the Nur Subfamily of Orphan Nuclear Receptors as a Novel Mechanism for Gene Activation

Abstract: We have recently shown that the orphan nuclear receptor Nur77 (NGFI-B) is most active in transcription when it is interacting with a cognate DNA sequence as a homodimer. Further, we have shown that the target for Nur77 dimers, the Nur response element (NurRE), is responsive to physiological stimuli in both endocrine and lymphoid cells, whereas other DNA targets of Nur77 action are not. The Nur77 subfamily also includes two related receptors, Nur-related factor 1 (Nurr1) and neuron-derived orphan receptor 1 (NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
250
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(262 citation statements)
references
References 48 publications
10
250
0
1
Order By: Relevance
“…Additionally, RXR is highly versatile with respect to its heterodimerization; among the many other nuclear receptors with which it can interact are two members of the orphan nuclear subfamily, Nur77 and Nurr1. These factors also function independently by binding Nur‐response elements, as monomers (NBRE) and dimers (NurRE) (Maira et al, 1999; Maira et al, 2003; Lefebvre et al, 2010). nFGFR1 forms CBP‐containing low mobility chromatin complexes with RXR, RAR, and Nurs.…”
Section: Ontogenic Programing Of Esc—role Of Ramentioning
confidence: 99%
“…Additionally, RXR is highly versatile with respect to its heterodimerization; among the many other nuclear receptors with which it can interact are two members of the orphan nuclear subfamily, Nur77 and Nurr1. These factors also function independently by binding Nur‐response elements, as monomers (NBRE) and dimers (NurRE) (Maira et al, 1999; Maira et al, 2003; Lefebvre et al, 2010). nFGFR1 forms CBP‐containing low mobility chromatin complexes with RXR, RAR, and Nurs.…”
Section: Ontogenic Programing Of Esc—role Of Ramentioning
confidence: 99%
“…Nur77, Nurr1 and Nor1 exhibit redundancy in many of their reported functions. 16,17 Moreover, previous microarray analyses of nuclear hormone receptor expression have demonstrated that, like Nur77, Nurr1 and Nor1 are rapidly and transiently induced in differentiating 3T3-L1 preadipocytes, raising the possibility that they may compensate for the loss of Nur77 in our cells. To test this, we employed an N-terminally truncated dominant-negative form of Nur77, which has been extensively characterized in several studies and exerts a strong dominant-negative effect against all members of the NR4A family.…”
Section: Introductionmentioning
confidence: 96%
“…To test this, we employed an N-terminally truncated dominant-negative form of Nur77, which has been extensively characterized in several studies and exerts a strong dominant-negative effect against all members of the NR4A family. [16][17][18] Wild-type and dominantnegative Nur77 (DN-Nur77) were subcloned into the retroviral pBabe vector, retroviruses were generated and used to infect 3T3-L1 preadipocytes to produce stable cell lines. Mock-transfected cells were generated by infection with empty virus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Nurr1 can modulate the expression of the DA transporter (DAT) and vesicular monoamine transporter (VMAT) (Hermanson et al 2003;Sacchetti et al 2001). Responsive elements sensitive to Nurr1 present in those gene promoters can also represent putative targets for other Nur members (Maira et al 1999;Perlmann and Jansson 1995). However, Nur77 (NR4A1) and Nor-1 (NR4A3) messenger RNA (mRNA) levels are extremely low in the substantia nigra (SN) and ventral tegmental area (VTA) in basal conditions (Zetterström et al 1996).…”
mentioning
confidence: 99%